1984
DOI: 10.1080/03079458408418563
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of osteopetrosis induced by virus strain Pts 56 in guinea fowl

Abstract: Avian osteopetrosis virus strain Pts 56 inoculated i.v. into 1 to 2-day-old guinea fowls induced bone growths (in up to 100% of birds). Their gross appearance and localisation differed markedly from osteopetrotic lesions in chickens and turkeys. Osteoblast proliferation in the periosteum as well as cell transformation into the chondral tissue were observed histologically. Periosteal bone formation, cartilage formation and endochondral ossification were observed to be taking place simultaneously or consecutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Route of 50% intranasal-conjunctivalj 50% intraperitoneal intranasal-conjunctival administration It has been shown that the guinea-fowl is susceptible to all common and well-known viral diseases of gallinaceous birds (among others, Tanyi, 1974;Lage et al, 1974;Pascucci et al, 1976;Nedyalkov, 1977;Nedyalkov et al, 1979;Yakimov et al, 1979;Geneste, 1981;Gough & Spackman, 1981;Ibragimov & Trubitsin, 1989;Misciattelli et al, 1981;Misciatelli et al, 1982;Pascucci et al, 1982;Kirev et al, 1983;Kirev, 1984;Watanabe & Ohmi, 1983;Toshkov et al, 1984;Cowen et al, 1988;Kles et al, 1988;Brahem et al, 1992). Pancreatitis aetiologically attributed to adenoviruses was reported in 3 to 4-week-old guineafowl (Reece & Pass, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Route of 50% intranasal-conjunctivalj 50% intraperitoneal intranasal-conjunctival administration It has been shown that the guinea-fowl is susceptible to all common and well-known viral diseases of gallinaceous birds (among others, Tanyi, 1974;Lage et al, 1974;Pascucci et al, 1976;Nedyalkov, 1977;Nedyalkov et al, 1979;Yakimov et al, 1979;Geneste, 1981;Gough & Spackman, 1981;Ibragimov & Trubitsin, 1989;Misciattelli et al, 1981;Misciatelli et al, 1982;Pascucci et al, 1982;Kirev et al, 1983;Kirev, 1984;Watanabe & Ohmi, 1983;Toshkov et al, 1984;Cowen et al, 1988;Kles et al, 1988;Brahem et al, 1992). Pancreatitis aetiologically attributed to adenoviruses was reported in 3 to 4-week-old guineafowl (Reece & Pass, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The only disease that produces a reactive endosteal bone tissue similar to that observed in our sample is avian osteopetrosis. This disease is a retrovirus‐induced bone disorder characterized by diaphyseal enlargement of the long bones, often associated with other gross histopathological alterations (Holmes, ; Bell and Campbell, ; Boyde et al, ; Frank and Franklin, ; Kirev, ). The histopathology and aetiology are different from those of mammalian osteopetrosis, which is genetically determined and is related to a failure of resorption of the bone deposited on the calcified cartilage of growth centers, resulting in the failure to produce a normal marrow cavity in the long bones (Tolar et al, ; Stark and Savarirayan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Avian osteopetrosis, instead, produces distinctive periosteal reactive bone deposition accompanied by endosteal bone deposits in the medullary cavity (although in some instances only endosteal reactive bone results) (Holmes, ). The microstructure of these reactive bones (periosteal and endosteal) is characterized by the presence of abundant and densely packed osteocyte lacunae, which are embedded in a poorly fibrous matrix (Bell and Campbell, ; Boyde et al, ; Kirev, ). Furthermore, Boyde et al () noted the presence of coatings of lamellar bone around the vascular spaces.…”
Section: Discussionmentioning
confidence: 99%
“…The histological features of the tumours studied revealed peculiarities in the response of guinea fowl towards MAV-2(0) and allowed some suggestions on the histogenesis of the bone lesions. The presence of both osteoblastic and chondroblastic differentiation and tumour bone formation in two interrelated ways, a peculiarity observed also in Pts-56-infected guinea fowl (Kirev, 1984) indicate that in this species the target cells of the virus effect are not likely to be undifferentiated osteogenic precursors. In chickens the same virus induces only proliferation of osteoblasts and osteoblast precursors (Boyde et al, 1978;Graf and Gauchy, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and type of the virus-induced bone lesions, however, are probably influenced by the sensitivity of the inoculated recipients. Heterologous infection of 1-to 2-day-old guinea fowl with avian osteopetrosis strain Pts-56 resulted in almost all cases in development of bone tumours which differed in gross appearance and in the localisation of the osteopetrotic lesions from the chicken (Nedyalkov et al, 1972;Kirev, 1984). Epithelial neoplasia of the pancreas and the duodenum were established in parallel with the bone growths in this species (Kirev et al, 1986(Kirev et al, ,1987.…”
Section: Introductionmentioning
confidence: 99%